PEMASARAN MENGUNAKAN MEDIA SOSIAL FACEBOOK PADA USAHA HOME INDUSTRY BERAS SIGER PEKON BUMI RATU - Dwi Puastuti; Novia Anggraeni; Muhammad Muslihudin; Citrawati Jatiningrum (Jurnal PkM Pemberdayaan Masyarakat, 2020)
Social media Facebook is nothing new in today's modern world. The role of social media is indeed very helpful for home industry players. Social media is currently transforming into a medium to create a new phenomenon in the economic world, including as a promotional media to buying and selling transactions, this has become a new force in the economic world where we can cut marketing costs by not reducing income even marketing can be more effective. The purpose of this paper is to find out how big the function of social media, especially Facebook, is in the development of e-commerce in Pekon Bumi Ratu. This Community Service activity aims to provide an understanding of how to market digital-based food products. From this activity, members who have a home industry business can market their products quickly, precisely, and safely so that customers can provide convenience to customers.